WAYS OF FORMING ORGANIZATIONAL AND ECONOMIC RELATIONS IN CONSTRUCTION ENTERPRISES - Tashimov A.Kh. (Scholar Express Journals, 2023)
In the article, proposals and recommendations have been developed on the improvement of the organizational and economic mechanisms of management in construction enterprises today, on the scientific-theoretical justification of many socio-economic relations in the improvement of the activities of construction industry enterprises
Keywords: construction industry; enterprises; organizational-economic mechanism